2023
DOI: 10.3390/su151310523
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Prioritization of Green Lean Supply Chain Management Factors Using Fuzzy DEMATEL

Abstract: Green–lean supply chain management (GLSCM) refers to strategically adopting and coordinating environmentally sustainable practices and lean concepts in supply chain operations. A considerable set of factors needs to be identified to implement GLSCM successfully. This study examined the factors influencing green lean supply chain management implementation in the Readymade Garments Industries of Bangladesh through a literature review and discussions with field experts. The fuzzy decision-making trial and evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 70 publications
(97 reference statements)
0
6
0
Order By: Relevance
“…Fuzzy DEMATEL helps in categorizing [112], determining causal relationships, prioritizing, and developing guidelines for logistics and supply chain operations, enhancing decision-making and system improvement [111]. Fuzzy logic is used by the Fuzzy DEMATEL approach to efficiently capture the priorities and intricate relationships among the elements, which helps managers develop plans and make wise decisions in many fields [42,[103][104][105][106][107][109][110][111][112]. It helps determine interdependencies, calculate weights, and address uncertainties, enhancing decision-making accuracy and effectiveness.…”
Section: Fuzzy Delphi-dematel Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fuzzy DEMATEL helps in categorizing [112], determining causal relationships, prioritizing, and developing guidelines for logistics and supply chain operations, enhancing decision-making and system improvement [111]. Fuzzy logic is used by the Fuzzy DEMATEL approach to efficiently capture the priorities and intricate relationships among the elements, which helps managers develop plans and make wise decisions in many fields [42,[103][104][105][106][107][109][110][111][112]. It helps determine interdependencies, calculate weights, and address uncertainties, enhancing decision-making accuracy and effectiveness.…”
Section: Fuzzy Delphi-dematel Methodsmentioning
confidence: 99%
“…The FDEMATEL is used in various fields such as public opinion evaluation [107] and hospital CRM readiness [108]. Fuzzy DE-MATEL is a valuable tool for analyzing factors influencing green lean supply chain management [109], improving supply chain resilience [110], and identifying barriers to sustainable supply chain management implementation in Iran [111]. Fuzzy DEMATEL helps in categorizing [112], determining causal relationships, prioritizing, and developing guidelines for logistics and supply chain operations, enhancing decision-making and system improvement [111].…”
Section: Proposed Methods and Frameworkmentioning
confidence: 99%
“…Successful green implementation is facilitated by developing a lean atmosphere. The researcher's primary concerns today include maintaining a green image, ecological balance and environmental sustainability (Hossain et al , 2023). Top management commitment (TMC) is essential in ensuring that an organisation’s goal is realised to the point of boosting the performance of industries.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…The study used Kappa statistics, created by Cohen [64], to ensure the consistency of the identified barriers across different perspectives, including managerial, information, integration, production, and environmental. In the previous literature, Tyagi et al [65] considered four perspectives, but Hossain et al [66] considered five perspectives, including environmental perspectives, to strengthen the sustainability performance. Kappa index (k) is a quantitative measure that assesses the level of agreement beyond chance by comparing observed and expected agreement.…”
Section: Reliability Analysismentioning
confidence: 99%